PENERAPAN METODE PREFERENCE SELECTION INDEX DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENINGKATKAN KEPUASAN KONSUMEN DENGAN MODEL CUSTOMER SATISFACTION INDEX (CSI) (Studi Kasus: Dealer Yamaha di Tasikmalaya) - Dimyati, Taopik; Hartono, Rudi; Supriatman, Agus (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. The growth of the motorcycle automotive industry is experiencing rapid growth which provides challenges for Yamaha dealers, especially in Tasikmalaya. The results of interviews and initial observations of staff and two customer samples from each dealer revealed several problems in the context of customer service. Such as difficulty communicating with technicians, unclear estimation of service time, limited availability of spare parts, unexplained additional costs and lack of information related to warranty or other promos. To determine the ranking of Yamaha dealers in Tasikmalaya based on customer satisfaction index values, a Decision Support System (SPK) and customer satisfaction index measurement techniques are needed. Customer Satisfaction Index (CSI) will be used to measure customer satisfaction and Preference Selection Index (PSI) approach will be used to support decision making in the Decision Support System (SPK). The CSI value in this study is 77.997 or 78% (Good). Yamaha Deta Singaparna dealer has the highest PSI value of 0.90251 so it ranks top. All dealers focus heavily on evaluating parking lot parameters, especially Yamaha Robbani Motor. It ranks the bottom with a score of 0.64258. The final result of this research shows that this problem can be solved by using the correlation between CSI and PSI approaches.